EVALUATION ON IMPLEMENTING THE PATIENT INFORMATION LEAFLET OF THE DIVISION OF INNOVATIVE HEALTH PRODUCTS AND SERVICES, THAI FOOD AND DRUG ADMINISTRATION - Lopongpanich, Thitipa; Sribundit, Namfon (Thai Bulletin of Pharmaceutical Sciences, 2023)
The purposes of this research were to evaluate the problems arising from implementing the patient information leaflet (PIL) of the Division of Innovative Health Products and Services, Thai Food and Drug Administration (Thai FDA) by the CIPP model (context, input, process and product evaluation) and to establish guidelines for implementing the PIL. Research was completed using a mixed quantitative method to collect data in October 2021 via an email link to a Google form questionnaire, which was sent to 150 subjects who worked in the areas of management, performance or who were marketing authorization holders. The data were analyzed by descriptive statistics such as mean and standard deviation. Quantitative data acted as a baseline to establish guidelines for implementing the PIL which used qualitative data. During December 2021, qualitative data were collected through in-depth interviews and focus groups, totaling 18 subjects. The data were analyzed by thematic analysis. The subjects completed and returned 135 questionnaires (90%). The main problem was that the cost of implementing the PIL user testing was too high. (Mean of the opinion’s score: 3.54±0.90; full score: 5.00). The second problem was that there were insufficient numbers of Thai FDA staff. (Mean of the opinion’s score: 3.10±1.24). For the qualitative research, the main problem aligned with the results of the quantitative research. Adding to the second problem is that there is a lack of personnel who have knowledge about the PIL. It is recommended that the Thai FDA increase the number of knowledgeable government officers and marketing authorization holders to mitigate these concerns. Thus, the Division of Innovative Health Products and Services should apply these findings to further development.